PENGARUH GOOD GOVERNANCE DAN PROFITABILITAS TERHADAP TOBIN Q DENGAN ENVIRONMENTAL DISCLOSURE SEBAGAI MODERASI - wiwik saraswati; Tutik Yuliani; Dimas Rama Pramudia; Tawakkal Chuarajab (KRISNA: Kumpulan Riset Akuntansi, 2024)
This study aims to examine and analyze the effect of environmental disclosure in mediating the relationship between governance and profitability on corporate value. The population in this study is all companies listed on the Indonesia Stock Exchange (IDX) for the period 2019 to 2022. The sample used in this study was 540 data. The results of this study show that governance and profitability mechanisms increase company value, meaning that investors tend to see governance mechanisms and profitability as signals in determining investment decisions. Environmental disclosure cannot increase the value of the company, investors do not view and environmental disclosure as an attractive issue and are considered to have no information content. The results of this study also prove that governance and profitability cannot increase corporate value through environmental disclosure. Keywords: environmental disclosure, corporate value, governance mechanism, profitability.